(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2011)
Тhe characteristics of activity of horned livestocks in Syunik marz, value of horned livestock impact on the environment particularly quantities of nitrogen and phosphorus and the possibility of cattle breeding development in this territory have been discussed.